2016
DOI: 10.1177/0706743716660290
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Network for Mood and Anxiety Treatments (CANMAT) 2016 Clinical Guidelines for the Management of Adults with Major Depressive Disorder

Abstract: For MDD of mild to moderate severity, exercise, light therapy, St. John's wort, omega-3 fatty acids, SAM-e, and yoga are recommended as first- or second-line treatments. Adjunctive exercise and adjunctive St. John's wort are second-line recommendations for moderate to severe MDD. Other physical treatments and natural health products have less evidence but may be considered as third-line treatments. CAM treatments are generally well tolerated. Caveats include methodological limitations of studies and paucity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(131 citation statements)
references
References 106 publications
(141 reference statements)
2
121
0
8
Order By: Relevance
“…Light therapy has repeatedly been shown to have an antidepressant effect in seasonal affective disorder (SAD), and also in nonseasonal depression, both as a monotherapy or when used as an adjunct to antidepressants [1,2,3,4,5]. The human physiology is very sensitive to both the intensity and the spectral wavelength composition of light, and even the LED backlight from laptops, which has a high amount of blue light, reduces sleepiness and notably influences circadian physiology when used in the evening [6].…”
Section: Introductionmentioning
confidence: 99%
“…Light therapy has repeatedly been shown to have an antidepressant effect in seasonal affective disorder (SAD), and also in nonseasonal depression, both as a monotherapy or when used as an adjunct to antidepressants [1,2,3,4,5]. The human physiology is very sensitive to both the intensity and the spectral wavelength composition of light, and even the LED backlight from laptops, which has a high amount of blue light, reduces sleepiness and notably influences circadian physiology when used in the evening [6].…”
Section: Introductionmentioning
confidence: 99%
“…Both therapies have been previously shown to be effective for treating depression (Leichsenring et al, 2016). But recent reviews found high dropout rates, low remission rates, and high placebo responses for these therapies (Mathew and Charney, 2009;Pigott et al, 2010;Rief et al, 2009;Turner et al, 2008); and complementary and alternative therapies can be a promising adjunct in the treatment of depression (Ravindran et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…El ejercicio físico aumenta el volumen cerebral del hipocampo (involucrado en el aprendizaje y la memoria), aumenta los niveles sanguíneos de algunas citocinas y afecta la neurotransmisión en pacientes con diagnóstico de depresión (13,14). En ese sentido, muchas investigaciones han demostrado una relación positiva entre el ejercicio físico y una mejoría en la depresión clínica y, actualmente, el mismo es considerado como un tratamiento de primera línea, incluso en monoterapia, para pacientes con depresión leve a moderada (1,14).…”
Section: Ejercicio Físico Y Depresiónunclassified